ELEVATED BLOOD LEAD LEVELS IN WOMEN OF REPRODUCTIVE AGE DUE TO LEADS EXPOSURE FROM CONTAMINATED WATER - Nursidika, Perdina; Kurnia, Dedeh; Sugihartina, Ganthina (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Water quality can decrease due to population growth, domestic waste handling, climate, and human activities. Most of the people in Cimahi use well water for drinking and eating. However, using well water with high lead levels for consumption can adversely affect on the lead levels in the women's blood of childbearing age. Purpose: This study investigates the relationship between lead levels in well water and the corresponding levels found in women's blood in the Leuwigajah area of Cimahi. Method: Research samples were collected from both well water and the women's blood of childbearing age (15 - 49 years) who consume well water for drinking and cooking. Subsequently, sample preparation was conducted, and the samples were analyzed using an atomic absorption spectrophotometer. The Spearman correlation test was employed to analyze the data and establish any potential correlations. Result: The lead content in water ranged from 0.055 ppm to 0.089 ppm, exceeding the requirements for lead in clean water. Meanwhile, lead levels in the blood ranged from 1.5 ug/dL to 78.2 ug/dL, with 6.7% falling within the normal category, 40% in the tolerable category, 30% in the excess category, and 23.3% in the high category. The statistical results show a significant relationship between lead levels in well water and the blood, with a correlation value of 37.9%. The correlation value indicates a weak positive relationship. Conclusion: There is a relationship between lead levels in well water and women's blood.